Technology and Production Fragmentation: Domestic versus Foreign Sourcing - Fort, Teresa C. (Review of Economic Studies, 2016)
This article provides direct empirical evidence on the relationship between technology and firms’ global sourcing strategies. Using new data on U.S. firms’ decisions to contract for manufacturing services from domestic or foreign suppliers, I show that a firm’s adoption of communication technology between 2002 and 2007 is associated with a 3.1 point increase in its probability of fragmentation. The effect of firm technology also differs significantly across industries; in 2007, it is 20% higher, relative to the mean, in industries with production specifications that are easier to codify in an electronic format. These patterns suggest that technology lowers coordination costs, though its effect is disproportionately higher for domestic rather than foreign sourcing. The larger impact on domestic fragmentation highlights its importance as an alternative to offshoring, and can be explained by complementarities between technology and worker skill. High technology firms and industries are more likely to source from high human capital countries, and the differential impact of technology across industries is strongly increasing in country human capital.